EFFECTIVE AND INTERACTIVE STRATEGIES TO ENHANCE READING AND COMPREHENSION SKILLS IN EFL CLASSROOMS - Abdubaitova Ruzigul (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract Reading comprehension is an essential academic skill and a key indicator of literacy development, particularly for learners of English as a Foreign Language (EFL). Traditional reading methods often fall short in engaging students and fostering deep understanding. This paper explores effective and interactive strategies aimed at improving reading comprehension, focusing on student-centered approaches such as reciprocal teaching, interactive read-alouds, literature circles, and the integration of technology. These methods support vocabulary development, critical thinking, and metacognitive awareness, ultimately creating more inclusive and effective reading environments.